A new approach for utilisation of single ERP to control multiple commands in BCI - Ahirwal, M.K.; Kumar, A.; Singh, G.K. (Taylor & Francis, 2014)
Decomposed Event Related Potential (ERP) analysis-based concept is proposed in order to increase the control commands corresponding to single ERP in Brain Computer Interface (BCI). Hypothesis based on analysis of Event-Related Spectral Perturbation (ERSP) is generalised with decomposed ERPs, and culminative power is estimated as features of decomposed ERPs.